December secrets - Giff, Patricia Reilly; Sims, Blanche (New York : Scholastic, 2006)
Each student in Ms. Rooney's room celebrates the December holidays by being a secret pal to a classmate.
"This edition is only available for distribution through the school market"--[P. 4] of cover.
Keywords: Friendship -- Juvenile fiction; Christmas stories; Hanukkah stories; Schools -- Juvenile fiction